Petrha+: A serious game to enhance physiotherapy students' clinical reasoning - Macedo, Rui (2022)
Role play and simulated patients are tools frequently used in undergraduate physiotherapy courses to help students gain familiarity with what they will find in future real-life encounters. However, these approaches have limitations when it comes to delivering diversity and repetition to a large number of students and are mostly bounded to the school’s premises. Web-based virtual patient software can help to overcome these shortcomings as they equally require students to go through most of the steps of the physiotherapy process, and simultaneously offer unlimited diversity of cases and repetition opportunities and can be delocalized from physical schools. PETRHA + is an Erasmus+ strategic partnership of European high education institutions aiming at the improvement of a web-based serious game prototype designed to enhance physiotherapy students’ clinical reasoning using virtual patients. The objective of this chapter is the presentation of the background context that led to the development of the serious game, its design features, functions, and ongoing and future developments.